Semiotics of Passions, Concepts and Perceptions - Hawi, Shahad Hassan; Al-Jumeily, Adnan Jassim Mohammed (Journal of Posthumanism, 2025)
Semiotics originated with De Saussure in his study of the relationship between the signifier and the signified, and Peirce who developed an expanded classification of signs. At that time, semiotics was concerned with the structure and active factors in discourse. However, a methodological deficiency later emerged in the form of the need to study emotions and passions. Semiotics developed with Greimas who presented the narrative. Then, his interest shifted to passions, which led to the emergence of semiotics of passions in order to understand emotions and their impact on shaping meaning, by relying on semiotic and psychological analysis to understand how emotions are represented in discourse, not just expressed. Therefore, using description and analysis as its methodology, the research aims to clarify the concept of semiotics of passions and the most important terms that were given to it and the references of its emergence, and its types.